Dynamic Mechanical Analysis of Synthetic epoxy (E) and Bio-epoxy Polymer Foam Integrated with Wood Filler Under 8000 hours Exposure to UV Irradiation - Mohd Rus, Anika Zafiah; Alzomor, Ashraf Abdo Qaid Abdullah; Abd Wahab, Hanani; Mohd Salim, Nurul Syamimi; Mohd Zaini, Ahmad Shahrizan Syah (Emerging Advances in Integrated Technology, 2025)
The  most  common  sustainable  solution  for  polyurethane  (PU)  materials  is  their  production  using renewable resources reducing the dependency on the consumption of petroleum-based oil products. This research presents results from an experimental study on the dynamic mechanical and viscoelastic properties such as storage modulus, E', loss modulus, E'' and damping coefficient, tan Î´ of syntactic epoxy (E) and bio-epoxy polymer foam loading with different ratio of flakes and powder filler 0, 5, 10, 15 and 20 %wt after exposed to UV irradiation for 8000  h.  Dynamic  mechanical  analysis  (DMA)  of  the  blended  were  performed  over  a  temperature  range  of  25â€“180Â°C for (E) and (B) polymer foam  under frequency of 1 Hz. The results demonstrated that the E20L specimen with the highest filler ratio gives the maximum storage modulus and loss modulus value (0.3125 MPa), (0.0625 MPa) respectively among other filler ratio due to bonding between foam and filler resulting in increased viscosity of the synthetic-epoxy PUs foam. Among  others,  the  bio-epoxy  PUs  foam  (B5P)  has  the  highest  storage  value (3.956 MPa) and loss modulus (17.213 MPa) indicating that bio-epoxy PU foams can dissipate energy faster than synthetic-epoxy  polymer  foams.  TG analysis  showed  that  the  synthetic  epoxy  (E)  polymer  foam  had higher  Tg value and E5L (1.2) archived  the highest value compared to the bio-epoxy foams which had much less repeatable results due to the less homogeneous structure of polyols.compulsory.